Oral Nutrition Supplements: Regulation and Distribution in Indonesia – a Study in a Private Hospital in Surabaya - Lama'ah Azzahra'; Nur Aisiyah Widjaja; Yasmine Nurfirdaus; Eva Ardianah; Edi Hermanto; Aziza Zahrotul Adha (Amerta Nutrition)
Background: Oral Nutrition Supplements (ONS) in the Minister of Health Regulation No. 29 year 2019 which was made as the guidance of nutritional management for children with nutritional problems, especially growth failure (still prevalent) and became one of Indonesia governments’ goal for MDG’s achievement.